Integrated Process for the Enzymatic Production of Fatty Acid Sugar Esters Completely Based on Lignocellulosic Substrates - Siebenhaller, Sascha; Kirchhoff, Jennifer; Kirschhöfer, Frank; Brenner-Weiß, Gerald; Muhle-Goll, Claudia; Luy, Burkhard; Haitz, Fabian; Hahn, Thomas; Zibek, Susanne; Syldatk, Christoph; Ochsenreither, Katrin (Frontiers in Chemistry, 2018)
Lignocellulose can be converted sustainably to fuels, power and value-added chemicals like fatty acid esters. This study presents a concept for the first eco-friendly enzymatic synthesis of economically important fatty acid sugar esters based on lignocellulosic biomass. To achieve this, beech wood cellulose fiber hydrolysate was applied in three manners: as sugar component, as part of the deep eutectic solvent (DES) reaction system and as carbon source for the microbial production of the fatty acid component. These fatty acids were gained from single cell oil produced by the oleaginous yeast Cryptococcus curvatus cultivated with cellulose fiber hydrolysate as carbon source. Afterwards, an immobilized Candida antarctica lipase B was used as the biocatalyst in DES to esterify sugars with fatty acids. Properties of the DES were determined and synthesized sugar mono- and di-esters were identified and characterized using TLC, MS and NMR. Using this approach, sugar esters were successfully synthesized which are 100 % based on lignocellulosic biomass.